Couples invoking shringara rasa surrounded by male and female attendants - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavaksha (horseshoe) motifs. Unlike other sections of the temple, the faces of the couples are not damaged and they are wearing heavy jewellery, elaborate hairstyle, and garments, indicating their royal lineage. The central male figure is seated in the lalitasana pose on a raised seat. The central female figure is seated on his thigh, looking towards the man with her head turned. Both rest their right feet on blooming lotus flowers. The man is holding a flower in his right hand while the woman gently rests her right hand on his left foot. Trees in the background suggest they are in a grove. The couple is surrounded by four male and female attendants. The female attendant in the top right is larger and is holding a sword in her right hand, indicating she is a warrior.